Surgical management of mallet finger with extension block pinning - Sadiq, Mohammed; Kulkarni, Vikrant (International Journal of Research in Orthopaedics, 2018)
Background: Various surgical and nonsurgical treatments have been described in the management of mallet finger. The purpose of this study is to evaluate the effectiveness of extension block pinning in the management of displaced mallet finger fractures. Methods: We conducted a retrospective study in which extension block pinning was done for displaced Mallet finger fractures. We included 10 patients in our study who were treated between 2016 and 2018. Fractures were classified according to Wehbe and Schnieder’s classification. All the procedures were done using ring block anaesthesia. Postoperative radiographic assessment was done at each follow up at 15 days interval. Wires were removed after radiologic confirmation of fracture healing. Assessment of the outcome was done using Crawford’s criteria. Results: According to Wehbe and Schnieder’s classification IIB type was the most common. All fractures involved more than 30% of articular surface. Average operative time was 30 mins. Congruent anatomical reduction was achieved in all the patients (intrarticular step off less than 1 mm). Average healing time of the fractures was 40 days. Seven out of the ten patients had excellent results. No wire related complications were seen in our patients. Conclusions: Extensor block pinning when performed accurately is an easy, economical and effective technique in treatment of mallet fingers.